Red blood cell, hemoglobin and heme in the progression of atherosclerosis - Jeney, Viktória; Balla, György; Balla, József (Frontiers in Physiology, 2014)
For decades plaque neovascularization was considered as an innocent feature of advanced atherosclerotic lesions, but nowadays growing evidence suggest that this process triggers plaque progression and vulnerability. Neovascularization is induced mostly by hypoxia, but the involvement of oxidative stress is also established. Because of inappropriate angiogenesis, neovessels are leaky and prone to rupture, leading to the extravasation of red blood cells (RBCs) within the plaque. RBCs, in the highly oxidative environment of the atherosclerotic lesions, tend to lyse quickly. Both RBC membrane and the released hemoglobin (Hb) possess atherogenic activities. Cholesterol content of RBC membrane contributes to lipid deposition and lipid core expansion upon intraplaque hemorrhage. Cell-free Hb is prone to oxidation, and the oxidation products possess pro-oxidant and pro-inflammatory activities. Defense and adaptation mechanisms evolved to cope with the deleterious effects of cell free Hb and heme. These rely on plasma proteins haptoglobin (Hp) and hemopexin (Hx) with the ability to scavenge and eliminate free Hb and heme form the circulation. The protective strategy is completed with the cellular heme oxygenase-1/ferritin system that becomes activated when Hp and Hx fail to control free Hb and heme-mediated stress. These protective molecules have pharmacological potential in diverse pathologies including atherosclerosis.